Kontekstualisasi Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Dalam Perspektif Islam - Shalihah, Aini; Khoyyinah (Journal of Law and Administrative Science, 2024)
Constitutional amendments in Muslim-majority countries, including Indonesia, often face political challenges, constitutional conflicts, and harmonisation between sharia principles and democratic values and civil liberties. This process reflects the complex socio-political dynamics of achieving a balance between tradition and modernity. This research aims to understand these challenges from an Islamic perspective, identify factors that influenced the amendment process, and explore the integration of Islamic principles with democratic values within a reformist constitutional framework. Using a qualitative approach and analysing relevant documents and literature studies, as well as conducting interviews with legal, political and religious experts, this research highlights the political tensions and conflicts related to human rights, governance structures, minority rights and religion. Despite challenges, there are opportunities to mediate sharia principles with democracy through constructive dialogue and compromise. The research also offers strategies to support constitutional reforms that take into account public welfare and democratic principles. Keywords:Constitution, Contextualization, Islam.